Efektivitas Aromaterapi Lemon untuk Mengatasi Emesis Gravidarum - Siti Rofi'ah; Sri Widatiningsih; Tuti Sukini (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2019)
Symptoms that often arise in the early months of pregnancy are nausea followed by vomiting (emesis). The content of Linalil in lemon aromatherapy is useful for normalizing the emotional state and unbalanced state of the body and functions as a sedative. The pungent odor caused by geranil acetate can stimulate the release of hormones that can calm and cause feelings of calm and affect the physical and mental changes of pregnant women so that complaints of nausea and vomiting are reduced.The aim of the study was to determine the effectiveness of lemon aromatherapy in overcoming the emesis of gravidarum. This type of research is quasy-experimental, in the form of Pretest-Postest with Control Group Design. Retrieval of research data using a closed questionnaire with Rhodes Index of Nausea Vomiting and Retching (INVR). Sampling with a total sampling of 46 patients was divided into 3 groups, namely 0.1 ml / 0.2 ml / 0.3 ml aromatherapy intervention. Processing data using ANOVA test.The results of the study state that there is no difference in the effectiveness of each dose of lemon aromatherapy in overcoming the emesis of gravidarum. Descriptively, there was a difference in changes in the score of nausea and vomiting in each dose group, namely 7; 17; 20.The results of this study are expected to be used as input for the Head of the Health Office in establishing policies on herbal medicine as a substitute for pharmacological drugs so that midwives can use alternative therapies to overcome complaints of nausea and vomiting in pregnant women. For companies herbal medicine can be used as a discourse to create herbal products, especially lemon aromatherapy with varied doses and affordable prices as a therapy to treat nausea and vomiting in pregnant women